2009
DOI: 10.1177/1940161209336225
|View full text |Cite
|
Sign up to set email alerts
|

Local Media, Public Opinion, and State Legislative Policies

Abstract: This study aims to explore first-level agenda setting at the state level. In particular, it examines the relationships among media coverage of local newspapers, state-level public opinion, and state legislative policies. In addition, it tests two state-level intervening factors: state legislative professionalism and state political culture. This study includes a geographic scope of eighteen U.S. states and a time period of twenty-two years from 1984 to 2006. The media agenda is represented by the news coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…In interviews with 36 top Australian public health practitioners (including experts in alcohol, obesity, and tobacco control), Chapman et al [24] explained how participants viewed the reach of media as surpassing any academic forum for research dissemination and policy influence. Tan and Weaver [25] corroborate that finding quantitatively, reporting a significant, strong, and positive correlation between newspaper coverage and the introduction of bills in the legislature of 14 observed American states between 1989 and 2006.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…In interviews with 36 top Australian public health practitioners (including experts in alcohol, obesity, and tobacco control), Chapman et al [24] explained how participants viewed the reach of media as surpassing any academic forum for research dissemination and policy influence. Tan and Weaver [25] corroborate that finding quantitatively, reporting a significant, strong, and positive correlation between newspaper coverage and the introduction of bills in the legislature of 14 observed American states between 1989 and 2006.…”
Section: Introductionsupporting
confidence: 70%
“…Across studies, the general population has increased support for public health interventions that have become established over time, that are less intrusive, and that are targeted at children and businesses as opposed to individuals [41]. At the same time, research shows that if strong public support for a policy is substantiated, policy influencers feel more comfortable supporting policy action [25]. Awareness of policy acceptability disconnects between policy influencers and the general public is invaluable for advocates looking to act on issues and to maximize policy windows, as it is known that public support plays a key role in ensuring the acceptability and sustainability of a policy [73].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…While there is a long--standing debate in media and political scholarship about whether news has strong or weak effects on a wide variety of outcomes (Bryant & Zillman, 2008) there is abundant evidence that news media can strongly influence public perception about the salience of issues (McCombs, 2004), the severity of public health threats (Young, Norman, & Humphreys, 2008), and affect community health behaviors (Abroms & Maibach, 2008;Chapman, 2007;Noar, 2006;Wallack & Dorfman, 1996). The media also influence political discourse and action, with discernible impacts on policy (Abroms & Maibach, 2008;Brewer & McCombs, 1996;Tan & Weaver, 2009). Alan Otten, for 44 years a reporter at The Wall Street Journal, observed that news reports can produce "public outrage (or policy maker outrage) that forces new regulations and laws or tougher enforcement of existing ones.…”
Section: Introductionmentioning
confidence: 99%